2021
DOI: 10.1037/tra0000953
|View full text |Cite
|
Sign up to set email alerts
|

Emotional resilience and event centrality mediate posttraumatic growth following adverse childhood experiences.

Abstract: Research has long established that adverse childhood experiences (ACEs) can lead to a range of negative psychological consequences, including post-traumatic stress (PTS) symptoms. It is also increasingly recognized that ACEs can serve as a catalyst for positive changes, such as post-traumatic growth (PTG). The mechanisms by which people report negative or positive changes are less well known. This study explored whether emotional resilience and event centrality could determine the degree of negative or positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 64 publications
0
20
0
3
Order By: Relevance
“…Overall, theories and empirical evidence support the mediational role of resilience between ACEs and psychological well-being; however, few studies have investigated mediation pathways. To the authors' best knowledge, only two studies specifically examined the mediational effect of resilience on the relationship between ACEs and psychological outcomes ( 33 , 47 ). Kelifa et al ( 33 ) study found that resilience partially mediated the relationship between ACEs and college students' depression in Eritrea such that ACEs were associated with reduced resilience, which subsequently exacerbated depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, theories and empirical evidence support the mediational role of resilience between ACEs and psychological well-being; however, few studies have investigated mediation pathways. To the authors' best knowledge, only two studies specifically examined the mediational effect of resilience on the relationship between ACEs and psychological outcomes ( 33 , 47 ). Kelifa et al ( 33 ) study found that resilience partially mediated the relationship between ACEs and college students' depression in Eritrea such that ACEs were associated with reduced resilience, which subsequently exacerbated depression.…”
Section: Introductionmentioning
confidence: 99%
“…Kelifa et al ( 33 ) study found that resilience partially mediated the relationship between ACEs and college students' depression in Eritrea such that ACEs were associated with reduced resilience, which subsequently exacerbated depression. Another study examined resilience as a mediator between ACEs and post-traumatic growth (PTG) in the U.K. and found that resilience mediated the effects of ACEs on individuals' PTG ( 47 ). Unfortunately, we did not find comparable evidence in a Chinese context.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudios reforzaron estas conclusiones (Allbaugh et al, 2016;Berntsen & Rubin, 2007a;Boals & Ruggero, 2016;Fitzgerald et al, 2016;Keshet & Gilboa-schechtman, 2019;Ogle et al, 2014b;Reiland, 2017). Sin embargo, un estudio realizado recientemente arroja resultados contradictorios a la mayoría de los estudios indicando que la Centralidad de los Eventos Traumáticos no se relacionaría a síntomas de TEPT en una muestra de individuos que sufrieron MI (Tranter et al, 2020).…”
Section: 1unclassified
“…En esta misma línea, un estudio de publicación reciente se propuso evaluar las relaciones entre el MI de tipo emocional, la Centralidad de los Eventos Traumáticos y las rumiaciones negativas en el desarrollo de síntomas de TEPT, obteniendo como resultado que el MI de tipo emocional influiría de forma indirecta en el desarrollo de los síntomas de TEPT por la vía de la centralidad de los eventos y las rumiaciones negativas (Watts et al, 2020). Contrariamente a lo sugerido por la mayoría de los estudios que se dedicaron a analizar las relaciones entre la centralidad de los eventos y el desarrollo de síntomas de TEPT, un estudio realizado sobre personas que sufrieron MI, mostró como resultado que la Centralidad de los Eventos Traumáticos no presentó asociaciones con los síntomas de TEPT, ni con la exposición a experiencias adversas en la infancia dentro de la que se incluyen distintos tipos de MI (Tranter et al, 2020). Este hallazgo polemiza con la mayoría de los estudios que componen la literatura y abre preguntas acerca de las relaciones entre el MI, la centralidad de los eventos y el TEPT.…”
Section: Centralidad De Los Eventos Traumáticos Y Trastorno De Estrés...unclassified
See 1 more Smart Citation